Measurement and spatio-temporal characteristics of ecosystem service value flow in yangtze river basin during 2010–2023: a network perspective - Wang, Miaowangyang; Lu, Xiangyi; Xie, Yao (Frontiers in Environmental Science, 2025)
Understanding the spatial flows of ecosystem services (ES) is essential for designing effective ecological compensation mechanisms. This study examines the spatial characteristics and evolution of ES flows in the Yangtze River Basin and their implications for transverse ecological compensation. Using the InVEST model to quantify ES supply and demand and a gravity model to simulate flow paths, we combined network analysis to identify critical nodes and bottlenecks. The results reveal a distinct “upstream supply–midstream transfer–downstream demand” gradient pattern. Upstream regions serve as primary suppliers and compensation beneficiaries, midstream regions function as transfer hubs, and downstream regions act as major demand areas and compensation contributors. From 2010 to 2023, the ES network evolved from a sparse structure into a complex polycentric system, with core nodes consolidating and secondary nodes emerging. Spatiotemporal analysis of ecological compensation shows a clear gradient with a general mitigation of supply–demand mismatch, indicating positive policy outcomes. This study recommends optimizing compensation criteria, enhancing the capacity of peripheral nodes, strengthening regional coordination, and balancing ecological and economic benefits to support sustainable ecological civilization development in the Yangtze River Basin.